2017
DOI: 10.1016/j.bmc.2016.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel multi-target indole-based derivatives as potent and selective inhibitors of chikungunya virus replication

Abstract: We recently identified indole derivatives (IIIe and IIIf) with anti-chikungunya virus (CHIKV) activities at lower micro molar concentrations and a selective index of inhibition higher than the lead compound Arbidol. Here we highlight new structural information for the optimization of the previously identified lead compounds that contain the indole chemical core. Based on the structural data, a series of indole derivatives was synthesized and tested for their antiviral activity against chikungunya virus in Vero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 26 publications
0
26
0
2
Order By: Relevance
“…46 Arbidol has both a novel mechanism of action and a different binding site to these drugs, as well as a low rate of generation of resistant strains of influenza with respect to adamantane and neuraminidase inhibitors. 14,15 As compound 11 shows a much higher binding affinity in the BLI than Arbidol, it is possible that drugs derived from this initial hit molecule would be far more effective in the treatment of influenza virus. Despite years of over-the-counter use in China and Russia to treat influenza, Arbidol resistance mutations have yet to be reported in the clinic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Arbidol has both a novel mechanism of action and a different binding site to these drugs, as well as a low rate of generation of resistant strains of influenza with respect to adamantane and neuraminidase inhibitors. 14,15 As compound 11 shows a much higher binding affinity in the BLI than Arbidol, it is possible that drugs derived from this initial hit molecule would be far more effective in the treatment of influenza virus. Despite years of over-the-counter use in China and Russia to treat influenza, Arbidol resistance mutations have yet to be reported in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…These have included changes to the nitrogen substituent, the hydroxy group in position 5, the bromo group in position 6, and the thiophenol in position 2. 1015 However, despite the large number of structure-activity relationship studies carried out to date, none of the compounds have shown a vast improvement in binding affinity to both group 1 and group 2 viruses over the parent compound Arbidol. This is perhaps not surprising as the exact binding site was unknown, although the mechanism of action was reported to involve increasing hemagglutinin (HA) stability through preventing the low pH-induced HA transition to the fusogenic state.…”
mentioning
confidence: 99%
“…[54][55][56] Additionally, the CHIKV surface consists of 80 trimeric spikes composed of heterodimers of the envelope glycoproteins (E 1 and E 2 ) in the lipid bilayer. [54][55][56] Additionally, the CHIKV surface consists of 80 trimeric spikes composed of heterodimers of the envelope glycoproteins (E 1 and E 2 ) in the lipid bilayer.…”
Section: Virology Of Chikungunya Virusmentioning
confidence: 99%
“…Based on results obtained by Di Mola et al, 71 new arbidol analogs were proposed by Scuotto et al 55 In this study, three new series of compounds were synthesized and evaluated against CHIKV in Vero cells using CPE assay ( Table 2). In addition, the E 2 unit of the crystal structure of the mature E 3 -E 2 -E 1 glycoprotein complex (PDB ID: 3N42) was used in the simulations (Gly407 corresponds to Gly82 in the crystal structure), two potential binding sites in the proximity of Gly82 were identified.…”
Section: Arbidol and Its Analogsmentioning
confidence: 99%
“…В настоящее время несколько научных групп в мире занимаются исследова-ниями «структура -активность» в ряду аналогов Арбидола с использованием различных методов [20,[22][23][24]. В част-ности, группа, получившая комплекс Арбидола с НА и изучившая его методом рентгено-структурного анализа [21], используя полученные данные о сайте связывания НА с Арбидолом, синтезировала его новые аналоги путем добавления метагидроксила к тиофенольной группе и замены новой группировкой молекулы воды в сайте свя-зывания, связь которых с НА была намного сильнее, чем связь Арбидола с НА [24].…”
Section: актуальность проблемы гриппозной инфекции успехи в терапии unclassified